Strategi Marketing Public Relations dalam Meningkatkan Brand Awareness - Pritha Hanum Fahny; Maman Suherman (UNISBA Press, 2022)
Abstract. PT X Bandung is a Marketing Communication Agency, a company that helps business people/entrepreneurs in marketing their products or brands through digital media, such as websites, social media, email, and others. This company has been established for 9 years, with this company it will help several companies that have difficulty carrying out promotional activities, sales, and other marketing activities. This study discusses efforts to increase brand awareness of PT. X Bandung through Marketing Public Relations. In this study, the authors use qualitative research methods that are descriptive and tend to use analysis. In this study, the author uses the theoretical basis to focus the research in accordance with the facts on the ground. The data collection technique used is through interviews by holding meetings to conduct questions and answers with resource persons, in addition to conducting interviews, namely there are observations, literature studies and online data searches. The results of this study, PT Progo uses Company Profile as product information that will be conveyed to prospective customers through structured planning. Determine the communication media to convey existing product information, namely through face-to-face media. The problem that exists is the lack of trust from consumers so that the solution used is two-way communication to get criticism and suggestions from consumers. Determining the target target is with nominal budgeting and